EFEKTIVITAS PENERAPAN PERMAINAN KECIL PADA PEMBELAJARAN PJOK UNTUK MENINGKATKAN HASIL BELAJAR BOLA VOLI SISWA KELAS XI F5 SMAN 7 KOTA JAMBI - Tindaon, Ratih R.N; Decheline, Grafitte; Ajanika, Yonifia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effectiveness of implementing small games to improve volleyball learning outcomes for class XI F5 students at SMA N 7 Jambi City in the 2025/2026 academic year. This study focuses on improving conventional teaching methods and the lack of student participation, resulting in the KKM score not being achieved. Data were obtained by distributing questionnaires to students (as primary data) and conducting interviews with physical education teachers (as supporting data). After all questionnaires were collected, the data were analyzed quantitatively using a percentage formula. Based on the results of the two research cycles, there were significant differences. In the initial action, only 4 students or 13% of the total 31 students achieved completeness. After implementing small games such as chain passing and volleyball, the number of students who completed in cycle I increased to 15 people with a percentage of 48%. However, because the target for class completion was 70%, the study continued to cycle II. In cycle II, the number of students who achieved completeness became 31 people with class completion reaching 100%. Existing data demonstrates that learning using mini-games can significantly increase the percentage of students completing their learning. This demonstrates that students' understanding and practice in learning using mini-games like chain passing and volleyball can improve student learning outcomes.